login
E.g.f. A(x) satisfies A(x) = 1/(exp(-x*A(x)^2) - x).
3

%I #16 Jan 09 2025 19:41:47

%S 1,2,15,223,5045,154161,5949715,277816813,15234148585,959821848433,

%T 68333878996991,5425649143910733,475370226250388221,

%U 45559752911807595865,4741534923025152367627,532526268840445510805341,64198018232238090097818065,8268729272698380485865553761

%N E.g.f. A(x) satisfies A(x) = 1/(exp(-x*A(x)^2) - x).

%F a(n) = n! * Sum_{k=0..n} (n+k+1)^(k-1) * binomial(n+k+1,n-k)/k!.

%o (PARI) a(n) = n!*sum(k=0, n, (n+k+1)^(k-1)*binomial(n+k+1, n-k)/k!);

%Y Cf. A377892, A379867.

%Y Cf. A088690.

%K nonn

%O 0,2

%A _Seiichi Manyama_, Jan 05 2025